W stronę przestrzennej teorii gatunków literackich - Elżbieta Konończuk (Zagadnienia Rodzajów Literackich, 2019)
The following article presents the literary theory of spatial genres, which emerged as a result of spatial turn. It discusses the concepts which link speech genres with a particular geographical location developed by Bakhtin, Szczukin, Moretti, Deguy and de Certeau. The aim of the article is to develop and reinforce the thesis which maintains that every genre has its own space and every space has its own genre. In order to prove the connection between geography and the morphology of a text the author analyzes the writings of Kenneth White, who in his geopoetic literary genetics searches for original genres to express, as he says, “poetic listening to nature”.